Djuna Barnes and Affective Modernism. - Taylor, Julie (Edinburgh University Press, 2012)
Explores the dynamic connections between the affective body and Djuna Barnes' textual corpus. Julie Taylor uses the writings of the American novelist, poet, dramatist, artist and journalist Djuna Barnes to form the basis of a series of disruptive questions about modernist aesthetics and the politics of reading. How do we reconcile Djuna Barnes' biographical writing with her Modernist commitment to impersonality? How do we honour the complexities of traumatic experience without pathologising the subject? How might we differently imagine the relationship between Modernism and literary history? Sh.